PENGARUH INFLASI DAN SUKU BUNGA TERHADAP KINERJA KEUANGAN BANK MUAMALAT INDONESIA PERIODE 2016-2020 - Sudin Yamani; Intan Hi. Tela Kye (Institut Agama Islam Negeri (IAIN) Ternate, 2022)
This study aims to determine the effect of inflation and interest rates on the financial performance of Bank Muamalat Indonesia (BMI). The inflation variable is measured by calculating the Consumer Price Index (CPI). The interest rate variable is measured by calculating the real interest rate. The performance variable is measured by calculating the return on assets of BMI from 2016-2020. This research method uses quantitative methods. The data used are secondary data in the form of published quarterly BMI financial ratio reports and published data on inflation as well as Bank Indonesia (BI) interest rates. Data were analyzed using multiple linear regression with the help of SPSS 22 to test the partial and simultaneous effect of 2 independent variables and 1 dependent variable. The results of this study indicate that the inflation variable partially has an effect on ROA and the interest rate variable has no effect on ROA. Simultaneously these two variables have no effect on ROA.